Empowerment of Youth Community Tourism Management in Sukamakmur District, Bogor Regency - Muhammad Zid; Asma Irma; Ode Sofyan Hardi; Sony Nugratama Hijrawadi (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The varied natural potential makes Bogor Regency has a lot of natural tourism potential. Its location in the highlands adds to the attraction of tourists to visit. One of the natural tourist destinations in Bogor Regency is Cipamingkis waterfall, the location of this waterfall is in Wargajaya Village, Sukamakmur District, Bogor Regency. Sukamakmur district actually has several tourist attractions, such as the Kahyangan villa and the Ciherang waterfall. However, the existence of this tourist attraction has not had a significant impact on the villagers, most of the villagers still rely on agricultural fields as their livelihood. In addition, the village youth have not played a role in the management of tourism objects. They prefer to work outside the village rather than develop their village. Therefore, this community service activity aims to provide training in managing and developing tourism objects in Sukamakmur district, the concept of community-based tourism management or better known as Community Based Tourism (CBT). The training was carried out in three stages, including program socialization, group discussions, and the last stage was tourism management planning. The results of these activities, in the socialization stage, the youth of Sukamakmur district actually have the motivation to manage and develop tourism objects in Sukamakmur district. However, it is constrained by limited knowledge about the management of tourism objects. The second stage of activity tries to dig up information on the existence of the tourist attraction, so that several alternative tourism development plans are obtained. In the last stage, it is activated to try alternative tourism objects that can be developed in Sukamakmur district with the hope that Sukamakmur district becomes a Tourism Village and residents get a positive impact.